Building Farmers’ Economic Resilience: The Role of Quality Seeds, Fertilizers, and Land Size in Increasing Farmers’ Income - Fauzi, Ahmad; Rosmiati, Sri; Juliansyah, Rollis (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to analyze the role of quality seeds, fertilizers, and land size in increasing farmers’ income, specifically in Kaway XVI District, West Aceh Regency. A quantitative method was employed, involving 96 randomly selected farmers as the sample. Primary data were collected through questionnaires, and the data were analyzed using multiple linear regression to evaluate the influence of each variable on farmers’ income. The results revealed that quality seeds did not have a significant effect on farmers’ income (p = 0.488 > 0.05), leading to the rejection of the first hypothesis (H1). In contrast, fertilizers had a significant impact on farmers’ income (p = 0.003 < 0.05), supporting the second hypothesis (H2). Additionally, land size also significantly influenced farmers’ income (p = 0.000 < 0.05), supporting the third hypothesis (H3). Collectively, the variables of quality seeds, fertilizers, and land size had a positive and significant influence on farmers’ income. These findings provide new insights into the study of farmers’ economic resilience, emphasizing the importance of optimizing fertilizer use and expanding land as key strategies to improve farmers’ income. Furthermore, the role of quality seeds requires further evaluation to understand other factors that may affect their effectiveness. This study recommends policy interventions focused on improving farmers’ access to quality fertilizers and efficient land management to support economic resilience in the agricultural sector.